Health outcomes among former female collegiate gymnasts: the influence of sport specialization, concussion, and disordered eating - Sweeney, E.; Howell, D. R.; Seehusen, C. N.; Tilley, D.; Case, E. (The Physician and Sportsmedicine, 2021)
Objective: Gymnastics is a popular sport with high injury rates, especially at the collegiate level. There is limited evidence, however, regarding the risks of early specialization in this sport, the rate of concussions in gymnasts, and the long-term effects of disordered eating in gymnasts. We sought to describe health-related outcomes of former collegiate gymnasts and the association with early sport specialization, concussion history, and disordered eating.